Utilization of Augmented Reality Technology as an Interactive Learning Media - Muhammad Iqbal Qatrunada; Muhammad Fadhlih Sephia Harasta; Ismail Tosofu (International Journal of Research and Applied Technology (INJURATECH), 2022)
This study discusses the use of augmented reality technology as an interactive learning medium. Innovative learning media at this time have a very important role in terms of improving the quality of learning. The main point in the use of information and communication technology, especially on mobile devices such as smartphones and android tablets which of course have camera features so that they can run augmented reality (AR) application technology. The purpose of this study was to analyze how the use of augmented reality technology in education midwives as an interactive learning medium that can support the learning process of students. This study uses qualitative research methods using data collection techniques through literature studies or commonly known as library research. In the research the results obtained are analytical descriptive because this research is a qualitative research. The results of this study are the application of information and communication technology in the form of augmented reality applications in the field of education as a learning medium that can help students in facilitating learning and creating a pleasant learning atmosphere.